Intertextuality: The Themes of Death, Sterility and Aridity in Eliot's The Waste Land As A Case Study - Hadi S. Sultan; Rai'a A. Abdul Aziz (PROSPECTIVE RESEARCHES, 2023)
Intertextuality is one of the literary terms which has recently received a special interest by literary critics all over the world. The present study tries to provide some definitions of this term and trace its origin and development. It also tries to draw a distinctive line between this term and some other terms and concepts, like influence, which, sometimes, overlap with it. It tackles its forms and mechanisms as they appear and work in themes of death, sterility and aridity in Eliot's The Waste Land. This study, however, concentrates on mythical, religious and literary intertextuality, for the poet absorbs, transforms, parallels and contrasts with some stories, situations and ideas in these sources. Accordingly, this paper is arranged.